The inhibition of interaction with serum albumin enhances the physiological activity of curcumin by increasing its cellular uptake. Issue 2 (21st December 2021) - Itaya, Mayuko; Miyazawa, Taiki; Khalifa, Saoussane; Shimizu, Naoki; Nakagawa, Kiyotaka
Abstract : Based on the free drug hypothesis, we hypothesized that food compounds that bind stronger to BSA than CUR inhibit the binding between BSA and CUR, and that this results in an increase of the cellular uptake and physiological activities of CUR. Abstract : Based on the free drug hypothesis, we hypothesized that food compounds that bind stronger to BSA than CUR inhibit the binding between BSA and CUR, and that this results in an increase of the cellular uptake and physiological activities of CUR. To verify this hypothesis, food compounds that bind stronger to BSA than CUR were identified. When THP-1 monocytes were co-treated with the identified compounds ( e.g., piperine) and CUR, cell viability significantly decreased, suggesting that the physiological activity of CUR was enhanced. Also, when THP-1 macrophages were co-treated with CUR and the identified compounds following LPS + IFNγ treatment, the decrement of TNF-α was higher compared to treatment with CUR only. Furthermore, the cellular uptake of CUR was increased during this co-treatment. Such results verify our hypothesis, and provide insights into the development of ways to enhance the physiological activities of various food compounds via focusing on their interaction with albumin.